Distribution of FMR1 and FMR2 repeats in 2 Argentinean patients with primary ovarian 3 insufficiency - Espeche, Lucía Daniela (2017)
The premutation state of FMR1 has been associated with Fragile X-related Premature Ovarian 29 Failure (POI) and is the most common known genetic cause for 46,XX patients. Nevertheless, very 30 few studies analyzed its frequency in Latin American populations. Additionally, a relationship 31 between alleles carrying a cryptic microdeletion in the 5?UTR of FMR2 and the onset of POI has only 32 been studied in one population. 33 Our aim was to analyze the incidence of FMR1 premutations and putative microdeletions in 34 exon 1 of FMR2 in a cohort of Argentinean women with POI. We studied 133 patients and 84 35 controls. Fluorescent PCR was performed and the FMR2 exon 1 was further sequenced in samples 36 presenting less than 11 repeats. We found the frequency of FMR1 permutations to be 6.7% and 37 2.9% for familial and sporadic patients, respectively. Among controls , 1/84 women presented a 38 premutation. In addition, although we did not find microdeletions in FMR2 , we observed a change 39 (T>C) adjacent to the repeats in two sisters with POI. Given the repetitive nature of the sequence 40 involved, we could not ascertain whether this represents a SNP or a deletion. Therefore, a 41 relationship between FMR2 and POI could not be established for our population.